A communication-free economical-sharing scheme for cascaded-type microgrids. (January 2019) - Li, Lang; Ye, Huawen; Sun, Yao; Han, Hua; Li, Xing; Su, Mei; Guerrero, Josep M.
Highlights: A communication-free economical-sharing scheme is proposed for cascaded-type microgrids. When the capacity constraints are not considered, the global optimization could be realized. When the capacity constraints are considered, a modification method is introduced near the boundary of feasible ranges. Abstract: This paper proposes an economical-sharing scheme without the needs of any communications for islanded AC microgrids (MGs) fed by cascaded inverters. The output voltage phase angle of each distributed generator (DG) is regulated by its corresponding incremental cost. Then the equal incremental principle used to guarantee the economic optimality is realized by synchronization conditions. In addition, a modification method is introduced with considering the capacity constraints. Stability analysis of the proposed method is carried out, and the conditions for economic optimality and stability are obtained. Because the communications are not needed, the advantages in cost and reliability are obvious. Simulations and experiments are implemented to verify the effectiveness of the proposed scheme.